Democracy and Apartheid - Butler, A. author. aut Link
IX, 212 p.
Keywords: South Africa's 1994 election was widely hailed around the world as miraculous. In this book, Anthony Butler examines South African experiences to cast doubt on this celebratory attitude to democracy. Contemporary political analysis highlights the benefits that democracy can sometimes bring. Butler, by contrast, argues that democracy can be malign. He attacks the myth that democracy ended apartheid, and shows that democratic practices themselves contributed to its evils. The author also explores weaknesses in political science as a discipline. This book will be essential reading for specialists in South Africa, and will appeal to political theorists, students of comparative politics, and historians.